Motivation : the organization of action - Mook, Douglas G., 1934- (New York : W. W. Norton, 1996)
This book is divided into four parts: The Concept of Motivation; Basic Action Systems; Purposive Behavior; and Human Motivation.
Keywords: Psychology; Motivation; Motivation (Psychology)